CELLULOSE SYNTHASE INTERACTING 1 is required for wood mechanics and leaf morphology in aspen. (10th July 2020) - Bünder, Anne; Sundman, Ola; Mahboubi, Amir; Persson, Staffan; Mansfield, Shawn D.; Rüggeberg, Markus; Niittylä, Totte
SUMMARY: Cellulose microfibrils synthesized by CELLULOSE SYNTHASE COMPLEXES (CSCs) are the main load‐bearing polymers in wood. CELLULOSE SYNTHASE INTERACTING1 (CSI1) connects CSCs with cortical microtubules, which align with cellulose microfibrils. Mechanical properties of wood are dependent on cellulose microfibril alignment and structure in the cell walls, but the molecular mechanism(s) defining these features is unknown. Herein, we investigated the role of CSI1 in hybrid aspen ( Populus tremula × Populus tremuloides ) by characterizing transgenic lines with significantly reduced CSI1 transcript abundance. Reduction in leaves (50–80%) caused leaf twisting and misshaped pavement cells, while reduction (70–90%) in developing xylem led to impaired mechanical wood properties evident as a decrease in the elastic modulus and rupture. X‐ray diffraction measurements indicate that microfibril angle was not impacted by the altered CSI1 abundance in developing wood fibres. Instead, the augmented wood phenotype of the transgenic trees was associated with a reduced cellulose degree of polymerization. These findings establish a function for CSI1 in wood mechanics and in defining leaf cell shape. Furthermore, the results imply that the microfibril angle in wood is defined by CSI1 independent mechanism(s). Significance statement: Mechanical properties of wood allow trees to grow tall and withstand a variety of environmental stresses. Understanding of the molecular machinery defining the mechanical properties of wood is important for tree breeding and wood industry. By combining functional genetics and mechanics we report here a new molecular link between cellulose biosynthesis and wood mechanics.